Incidence, Etiology, and Severity of Acute Gastroenteritis Among Prospectively Enrolled Patients in 4 Veterans Affairs Hospitals and Outpatient Centers, 2016–2018. (15th June 2020) - Cardemil, Cristina V; Balachandran, Neha; Kambhampati, Anita; Grytdal, Scott; Dahl, Rebecca M; Rodriguez-Barradas, Maria C; Vargas, Blanca; Beenhouwer, David O; Evangelista, Karen V; Marconi, Vincent C; Meagley, Kathryn L; Brown, Sheldon T; et al.
Abstract: Background: Acute gastroenteritis (AGE) burden, etiology, and severity in adults is not well characterized. We implemented a multisite AGE surveillance platform in 4 Veterans Affairs Medical Centers (Atlanta, Georgia; Bronx, New York; Houston, Texas; and Los Angeles, California), collectively serving >320 000 patients annually. Methods: From 1 July 2016 to 30 June 2018, we actively identified inpatient AGE case patients and non-AGE inpatient controls through prospective screening of admitted patients and passively identified outpatients with AGE through stool samples submitted for clinical diagnostics. We abstracted medical charts and tested stool samples for 22 pathogens by means of multiplex gastrointestinal polymerase chain reaction panel followed by genotyping of norovirus- and rotavirus-positive samples. We determined pathogen-specific prevalence, incidence, and modified Vesikari severity scores. Results: We enrolled 724 inpatients with AGE, 394 non-AGE inpatient controls, and 506 outpatients with AGE. Clostridioides difficile and norovirus were most frequently detected among inpatients (for AGE case patients vs controls: C. difficile, 18.8% vs 8.4%; norovirus, 5.1% vs 1.5%; P < .01 for both) and outpatients (norovirus, 10.7%; C. difficile, 10.5%). The incidence per 100 000 population was highest among outpatients (AGE, 2715; C. difficile, 285; norovirus, 291) and inpatients ≥65 years old (AGE, 459; C. difficile, 91; norovirus, 26). Clinical severity scores were highest for inpatient norovirus, rotavirus, and Shigella /enteroinvasive Escherichia coli cases. Overall, 12% of inpatients with AGE had intensive care unit stays, and 2% died; 3 deaths were associated with C. difficile and 1 with norovirus. C. difficile and norovirus were detected year-round with a fall/winter predominance. Conclusions: C. difficile and norovirus were leading AGE pathogens in outpatient and hospitalized US veterans, resulting in severe disease. Clinicians should remain vigilant for bacterial and viral causes of AGE year-round. Abstract : We prospectively enrolled patients with acute gastroenteritis (AGE) at 4 Veterans Affairs Medical Centers over a 2-year period. Clostridioides difficile and norovirus were leading AGE pathogens in outpatients and inpatients and resulted in severe disease, intensive care unit stays, and deaths.